Enhancing asphalt binder performance through nano-SiO2 and nano-CaCO3 additives: Rheological and physical insights - Ahmed Mahir Mohammed; Alaa H. Abed (Case Studies in Construction Materials, 2023)
During the last two decades, nanomaterial application has gained a significant attraction into asphalt technology due to their effect in enhancing asphalt binder improving the asphaltic mixture. This study will modify the asphalt binder with two different nano types, nano SiO2 and CaCO3, at levels ranging from 1% to 7%. The resulting optimum nano-modified Asphalt will be subject to a series of rheological tests, including dynamic shear rheometer (DSR), Viscosity, and bending beam rheometer (BBR) to determine asphalt binder sensitivity towards low-medium-high temperature range. Results indicate that both nano types improved the physical characteristics of Asphalt, and 5% by weight of Asphalt was suggested as a reasonable dosage of nano-SiO2 and nano-CaCO3 based on the overall desirability analysis of physical tests. The viscosity and temperature sensitivity of bitumen were improved by adding nano SiO2 and CaCO3. On the other hand, the asphalt rutting resistance's capabilities were improved at higher temperatures. In contrast, it decreases resistance against fatigue at intermediate temperatures due to the lowest phase angles and higher loss moduli. The BBR test, however, reveals a modest decrease in bituminous anti-cracking.